YEAST EXTRACT ELICITATION ENHANCES METABOLITE PRODUCTION IN Alocasia cuprea CALLUS - Zozy Aneloi Noli; Suwirmen; Lily Ismaini; Meza Rani Maudya (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTSYeast extract boosts metabolitesEnhances bioactive yieldBest at moderate dose (150 mg/L)ABSTRACTAlocasia cuprea is a tropical ornamental plant species belonging to the family Araceae, widely recognized for its distinctive and aesthetically appealing foliage. Additionally, it represents a promising source of bioactive metabolites. This study aimed to evaluate the potential of yeast extract elicitation for enhancing metabolite production in A. cuprea callus culture established through in vitro propagation. The methods used in this study included callus induction, elicitation treatments, and phytochemical analysis of A. cuprea callus. The experiment was conducted using a completely randomized design (CRD) consisting of five yeast extract concentrations (0, 50, 100, 150, and 200 mg/L) with six replications. The results revealed that elicitation treatment did not affect callus biomass. Morphologically, the callus exhibited a friable texture and changed in color from off-white to yellowish-brown following elicitation. However, elicitation increased both the yield and diversity of metabolites in A. cuprea callus cultures. The optimal yeast extract concentration for enhancing the accumulation of major metabolites in A. cuprea was 150 mg/L. At this concentration, the levels of n-hexadecanoic acid, 9,12-octadecadienoic acid (Z,Z)-, and squalene increased by 6.67%, 82.49%, and 291.60%, respectively, compared with control. Nevertheless, the accumulation patterns of individual compounds varied across treatments, indicating that each metabolite exhibits a specific biosynthetic response to variations in yeast extract concentration.